The Printmakers of Atelier 17. (London : Austin/Desmond Contemporary Books)
Brignoni, Serge ; Buckland-Wright, John ; de Caro, Anita ; Courtin, Pierre ; Grippe, Peter ; Hayter, Stanley William ; Husband, Dalla ; Kohn, Misch ; Masson, André ; Mead, Roderick ; etc.
Engels
boek